Ten Triangles around Cavernous Sinus for Surgical Approach, Described by Schematic Diagram and Three Dimensional Models with the Sectioned Images - Chung, Beom Sun; Ahn, Young Hwan; Park, Jin Seo (Journal of Korean medical science, 2016)
For the surgical approach to lesions around the cavernous sinus (CS), triangular spaces around CS have been devised. However, educational materials for learning the triangles were insufficient. The purpose of this study is to present educational materials about the triangles, consisting of a schematic diagram and 3-dimensional (3D) models with sectioned images. To achieve the purposes, other studies were analyzed to establish new definitions and names of the triangular spaces. Learning materials including schematic diagrams and 3D models with cadaver's sectioned images were manufactured. Our new definition was attested by observing the sectioned images and 3D models. The triangles and the four representative surgical approaches were stereoscopically indicated on the 3D models. All materials of this study were put into Portable Document Format file and were distributed freely at our homepage (anatomy.dongguk.ac.kr/triangles). By using our schematic diagram and the 3D models with sectioned images, ten triangles and the related structures could be understood and observed accurately. We expect that our data will contribute to anatomy education, surgery training, and radiologic understanding of the triangles and related structures.